2016
DOI: 10.3389/fphys.2016.00625
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acidified Blood Using Reduced Osmolarity Mixed-Base Solutions

Abstract: We hypothesize that reduced osmolarity mixed-base (ROMB) solutions can potentially serve as customizable treatments for acidoses, going beyond standard solutions in clinical use, such as 1.0 M sodium bicarbonate. Through in silico quantitative modeling, by treating acidified canine blood using ROMB solutions, and by performing blood-gas and optical microscopy measurements in vitro, we demonstrate that ROMB solutions having a high proportion of a strong base, such as disodium carbonate or sodium hydroxide, can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…However, in practice, manifestation of the side effects associated with NaHCO 3 administration is not a foregone conclusion [61] , [62] . Alternative vehicles for intravenous alkali delivery such as Na 2 CO 3 and CaCO 3 produce less CO 2 per neutralized H + and impose less of an osmotic stress [63] . Carbicarb is a mixture of NaHCO 3 and Na 2 CO 3 that does not cause intracellular acidification [64] , [65] .…”
Section: Systemic Acid-base Disturbancesmentioning
confidence: 99%
“…However, in practice, manifestation of the side effects associated with NaHCO 3 administration is not a foregone conclusion [61] , [62] . Alternative vehicles for intravenous alkali delivery such as Na 2 CO 3 and CaCO 3 produce less CO 2 per neutralized H + and impose less of an osmotic stress [63] . Carbicarb is a mixture of NaHCO 3 and Na 2 CO 3 that does not cause intracellular acidification [64] , [65] .…”
Section: Systemic Acid-base Disturbancesmentioning
confidence: 99%
“…Development of additional bases with beneficial properties might also prove useful in the treatment of acidemia. 23 Finally, the reduction in intracellular pH during acute acidemia might impair cellular function, not only by compromising the function of critical cellular enzymes and other proteins, but also by accelerating the activity of proteins or pathways that could be deleterious. Studies in animals have indicated that activation of the myocardial sodium/hydrogen exchanger 1 (NHE1) during lactic acidosis contributes to cellular dysfunction and mortality.…”
Section: How Does This Study Compare With Prior Studies?mentioning
confidence: 99%